2021
DOI: 10.3390/sym13101792
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Handedness Genetics

Abstract: Around the world, about 10% people prefer using their left-hand. What leads to this fixed proportion across populations and what determines left versus right preference at an individual level is far from being established. Genetic studies are a tool to answer these questions. Analysis in twins and family show that about 25% of handedness variance is due to genetics. In spite of very large cohorts, only a small fraction of this genetic component can be pinpoint to specific genes. Some of the genetic association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Parent-offspring regression in ALSPAC also showed significant heritability for handedness and footedness when using the quantitative phenotypes. We conclude that the quantitative phenotypes are better suited to capture the polygenic nature of handedness as expected under a liability threshold model [ 67 ]. The lack of association between the PRS derived from a recent large-scale GWAS for categorical handedness [ 24 ] suggests the influence of separate genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Parent-offspring regression in ALSPAC also showed significant heritability for handedness and footedness when using the quantitative phenotypes. We conclude that the quantitative phenotypes are better suited to capture the polygenic nature of handedness as expected under a liability threshold model [ 67 ]. The lack of association between the PRS derived from a recent large-scale GWAS for categorical handedness [ 24 ] suggests the influence of separate genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this provocative question remains elusive. Genetic explanations, including those arising from genomewide association studies, although traditionally popular in handedness research, have not revealed any compelling answer to this question (Cuellar-Partida et al, 2021; de Kovel & Francks, 2019; Paracchini, 2021).…”
mentioning
confidence: 99%
“…Moreover, additive genetic factors explain only one quarter of the variance in human handedness, and it has been suggested that nonshared environmental factors can explain part of the remaining variance 20 , 115 (but see Refs. 116 118 ). Hence, to understand the ontogeny of functional and brain lateralization we must elucidate the interaction between endogenous and environmental factors 2 , 3 , 11 , 14 , 17 , 66 , 67 , 69 71 .…”
Section: Discussionmentioning
confidence: 99%